Collisional-legal questions of protection of cultural heritage (International relations and international law Journal, 2016)
The article is dedicated to the collisional-legal questions of protection of cultural heritage. It analisys objective and liability statute of cultural resourses. Regarding this the article reviews features of common collisional principles which can be applied. Accordingly, there is provided comparative analisys of international private law legislation of Azerbaijan Republic and other states.The article also analyses existing in modern legal literature suppositions regarding private collisional prinsiples dealt with the protection of cultural heritage and substanciate the use of the law of state of origin (lex origins) principle.
Keywords: cultural heritage; cultural resources; collision principles; collision problems; place of location of property; right of the state of origin